2016
DOI: 10.1177/0042085916674059
|View full text |Cite
|
Sign up to set email alerts
|

Too Scared to Learn? The Academic Consequences of Feeling Unsafe in the Classroom

Abstract: A safe environment is a prerequisite for productive learning. Using a unique panel data set of survey responses from New York City middle school students, the article provides insight into the relationship between feelings of safety in the classroom and academic achievement. The survey data include the reported feelings of safety for more than 340,000 students annually from 2007 to 2010 in more than 700 middle schools. Findings show a consistent negative relationship between feeling unsafe in the classroom and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
0
46
0
2
Order By: Relevance
“…Three separate studies have used child-, family-, or neighborhood-fixed effects to estimate how changes in exposure to community violence are associated with child behavior or performance in school. Lacoe (2016) drew on a data set that tracks public school students in New York City over successive academic years and utilized both student-and classroom-fixed effects to identify how feelings of safety in school are linked with academic achievement. In student-fixed effects models, Lacoe found that in years when students reported feeling unsafe in school their performance on standardized achievement tests declined.…”
Section: Identifying the Impact Of Exposure To Violent Environmentsmentioning
confidence: 99%
“…Three separate studies have used child-, family-, or neighborhood-fixed effects to estimate how changes in exposure to community violence are associated with child behavior or performance in school. Lacoe (2016) drew on a data set that tracks public school students in New York City over successive academic years and utilized both student-and classroom-fixed effects to identify how feelings of safety in school are linked with academic achievement. In student-fixed effects models, Lacoe found that in years when students reported feeling unsafe in school their performance on standardized achievement tests declined.…”
Section: Identifying the Impact Of Exposure To Violent Environmentsmentioning
confidence: 99%
“…The evidence suggests that four primary dimensions of school climate are likely to influence student performance: school-based violence and disorder, school safety, school discipline, and sense of community within the school. Specifically, in New York City, feeling unsafe at school decreases the academic achievement of middle school students, and the largest effects are found in schools with the most school-based violence (Lacoe 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on care shows it is highly correlated with educational, emotional, and physical development (whether in school, family, health, etc.) [48,49]. Given these correlations, it is convenient for educational policy and investment (i.e., the state and capital) to define care as an attribute some teachers have and others do not.…”
Section: "Girls Like Me": Structural Determinants Of Meaningful Intermentioning
confidence: 99%